Government Response in Cases of Sexual Violence: Systematic Literature Review - Trivianti Lestari; Asep Sumaryana; Candradewini (Universitas Medan Area, 2023)
This research raises the issue of sexual violence in several countries by looking at how the government responds to it. This research also collects recommendations for the government and what approaches are appropriate to the problems that occur. The research method in this paper uses a systematic literature review originating from the Scopus database without extracting documents in all countries. As a result, there are 11 journal articles related to the government's response to cases of sexual violence in several countries, including New Zealand, Australia, Nigeria, South Africa, Greece, Korea and several other countries around the world. This article aims to look at the trend of research publication related to cases of sexual violence around the world. In cases of sexual violence, there are different background problems in each country, such as those resulting from cases of slavery, terrorism, the Covid-19 pandemic to migration. There are very few articles that raise the issue of the government's response to cases of sexual violence, so more research is needed in the future.